Acerca de la Metodologia de Investigacion en la Historia de la Psicologia. - Klappenbach, Hugo Alberto Arturo (2014)
The paper begins by analyzing the main research trends in the field of the history of psychology and the classical opposition between Whig historiography and critical historiography. Afterwards, it analyzes the various stages of the research methodology used in the field of the history of psychology. In order to do this, the research activities of the historian of psychology are compared to those conducted in both the natural sciences and the social sciences. As a result of this comparative analysis, it is possible to conclude that the stages of the research methodology applied in the field of the history of psychology coincide to some extent with the stages of the research methodology used in other scientific fields.